Respuesta :

Answer:

3x²-11x-14=0  

Step-by-step explanation:

Given equation is : (3x²+6x+7)-(6x²-5x-7)

Putting the equation equals to zero making it in the form of polynomial equation (3x²+6x+7)-(6x²-5x-7)=0

Opening the bracket of the equation, the negative sign outside the bracket changes the sign of the values after opening the bracket.

                3x²+6x+7-6x²+5x+7=0

Solving this by subtracting the values of same type i.e subtracting the component of x having the same power.

                3x²-6x²+6x+5x+7+7=0

                              -3x²+11x+14=0    OR   3x²-11x-14=0  

So, on subtracting the above equation the quadratic equation is obtained 3x²-11x-14=0